Teachers’ Expectations and Acceptance of a Home-grown Networked Automated Essay Scorer with Feedback (AESF) for the Malaysian University English Test (MUET) Classroom - Ng, Sing Yii; Hong, Kian Sam; Lee, Nung Kion; Bong, Chih How (Malaysian English Language Teaching Association (MELTA), 2015)
When introducing any online system into the classroom, teachers’ acceptance and expectations are the prerequisites for its success because teachers are the ones who implement the system. They are the driving forces that ensure the system is used, works and serves its purposes. This study aimed to determine teachers’ acceptance of, and expectations about the introduction of an automated networked-based essay scorer that provides immediate feedback in terms of scores and remarks called the Automated Essay Scoring Feedback (AESF). A total of eight experienced MUET teachers were selected to be interviewed. The qualitative findings were analysed, coded and trended. One of the findings indicates that essay writing is the most underdeveloped skills because it is demanding on the students and teachers who have to guide, assess, respond and document their students’ writing. The proposal of a home-grown and networked AESF was positively accepted by the teachers despite being sceptical about the reliability and other technical issues. Some practical considerations that emerged from the study that contribute towards the design and development of AESF, include the need for immediacy, ease of use, usefulness, and reliability and validity. Being home-grown, AESF can overcome a fundamental drawback of commercially available Automated Essay Scorer (AES), namely cultural sensitivity and validity.